2016
DOI: 10.4236/msce.2016.47013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wood Ash on Properties of Concrete and Flowable Fill

Abstract: This research investigated the use of wood ash to partially replace cement or sand in conventional concrete, roller compacted concrete (RCC), and flowable fill. The main focus was to determine how the wood ash addition affected the main fresh and hardened properties of these materials. It was found that the wood ash could be successfully incorporated into the conventional concrete. In particular, the wood ash addition not only accelerated the setting, but also improved the early and the 28-day compressive stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…These materials are characteristic of CDW residues and, according to some authors, can influence concrete properties. The amount of wood can increase WA and decrease CS [40]. The addition of Styrofoam to the concrete can reduce its density, and consequently decrease CS as well as improve its thermal conductivity [41,42].…”
Section: Characterization Of Cdwmentioning
confidence: 99%
“…These materials are characteristic of CDW residues and, according to some authors, can influence concrete properties. The amount of wood can increase WA and decrease CS [40]. The addition of Styrofoam to the concrete can reduce its density, and consequently decrease CS as well as improve its thermal conductivity [41,42].…”
Section: Characterization Of Cdwmentioning
confidence: 99%
“…An overview of recent studies [3] showed that WA is acceptable as an alternative replacement to cements and concrete aggregates due to its high silica content [4,5]. It was shown that WA could be used as a pozzolan up to 20 wt.% [6,7] and as an additive up to 10 wt.% [8] to obtain concrete material with optimal characteristics as well as to reduce price and CO 2 emissions [9]. However, it is determined [10] that such WA has averagely only 6.30 wt.% of spherical particles; therefore, its usage as a pozzolanic additive in concretes is limited.…”
Section: Introductionmentioning
confidence: 99%
“…The disposal costs of the ash are rising and volume of ash is increasing, a sustainable ash management which integrates the ash within the natural cycles needs to be employed [4][5][6].The utilization of pozzolanic materials like fly ash, GGBS, metakaolin and rice husk ash in cement and concrete manufacturing was implemented for several decades [7][8][9][10][11]. Wood ash is pozzolanic material, it can blend in concrete partially by cement [12][13]. Recent studies on the use of wood ash as a new brick material supplement appear to be a viable solution not only to the environmental problem but also to the problem of to economic design of buildings [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%